Massage Counterpresure Efektif Menurunkan Nyeri Inpartu Kala I - Susilowati, Nesya; Kamidah, Kamidah (Indonesian Journal on Medical Science, 2024)
The birthing process is a process where a mother is eagerly awaiting it. Labor pain is a physiological condition that causes discomfort due to the stimulation of certain nerve endings. Counterpressure massage is a non-pharmacological technique that can be applied to mothers giving birth, which can provide pleasant feelings and combat discomfort during contractions or between contractions during labor. This study aims to determine the effect of the counterpressure massage method on reducing pain in mothers in the first stage of birth. Research with a cross-sectional approach uses a pre-experimental design with a one-group pre-test-post-test design. On average, pain in laboring mothers decreased after a counterpressure massage was carried out. The results of the analysis showed that there was a difference in pain intensity before and after the intervention was given. So, it can be concluded that counterpressure massage is effective in reducing pain in the first stage of labor.